The proneural transcription factor ASCL1 regulates cell proliferation and primes for differentiation in neuroblastoma - Parkinson, Lydia M.; Gillen, Sarah L.; Woods, Laura M.; Chaytor, Lewis; Marcos, Daniel; Ali, Fahad R.; Carroll, Jason S.; Philpott, Anna (Frontiers in Cell and Developmental Biology, 2022)
Neuroblastoma is believed to arise from sympathetic neuroblast precursors that fail to engage the neuronal differentiation programme, but instead become locked in a pro-proliferative developmental state. Achaete-scute homolog 1 (ASCL1) is a proneural master regulator of transcription which modulates both proliferation and differentiation of sympathetic neuroblast precursor cells during development, while its expression has been implicated in the maintenance of an oncogenic programme in MYCN-amplified neuroblastoma. However, the role of ASCL1 expression in neuroblastoma is not clear, especially as its levels vary considerably in different neuroblastoma cell lines. Here, we have investigated the role of ASCL1 in maintaining proliferation and controlling differentiation in both MYCN amplified and Anaplastic Lymphoma Kinase (ALK)-driven neuroblastoma cells. Using CRISPR deletion, we generated neuroblastoma cell lines lacking ASCL1 expression, and these grew more slowly than parental cells, indicating that ASCL1 contributes to rapid proliferation of MYCN amplified and non-amplified neuroblastoma cells. Genome-wide analysis after ASCL1 deletion revealed reduced expression of genes associated with neuronal differentiation, while chromatin accessibility at regulatory regions associated with differentiation genes was also attenuated by ASCL1 knock-out. In neuroblastoma, ASCL1 has been described as part of a core regulatory circuit of developmental regulators whose high expression is maintained by mutual cross-activation of a network of super enhancers and is further augmented by the activity of MYC/MYCN. Surprisingly, ASCL1 deletion had little effect on the transcription of CRC gene transcripts in these neuroblastoma cell lines, but the ability of MYC/MYCN and CRC component proteins, PHOX2B and GATA3, to bind to chromatin was compromised. Taken together, our results demonstrate several roles for endogenous ASCL1 in neuroblastoma cells: Maintaining a highly proliferative phenotype, regulating DNA binding of the core regulatory circuit genes to chromatin, while also controlling accessibility and transcription of differentiation targets. Thus, we propose a model where ASCL1, a key developmental regulator of sympathetic neurogenesis, plays a pivotal role in maintaining proliferation while simultaneously priming cells for differentiation in neuroblastoma.